The Synthesis of Iodbenzimidazoles and Iodbenzoxazoles via Iodination of Arenediazonium Tosylates; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Hong N. T. T. (Chemical Technologies, 2014)
Title screen